Analysis and design of an interior permanent magnet synchronous machine with double-layer PMs for electric vehicles based on multi-physics fields. Issue 1 (2nd January 2018) - Li, Ya; Liu, Xiping; Liu, Zhangqi
Abstract : Purpose: This paper aims to present an interior permanent magnet synchronous machine (IPMSM) with double-layer PMs used for electric vehicles, of which the integrated simulation of electromagnetic field, stress field and temperature field are analyzed. Design/methodology/approach: Some electromagnetic characteristics including iron loss, efficiency and flux linkage are obtained by finite element analysis. The mechanical strength of rotor at the maximum speed and the temperature rise at the rated load are calculated by three-dimensional finite element analysis (FEA). Findings: The results show that the presented IPMSM can work with sufficient mechanical strength, machine temperature rise and high efficiency during field-weakening operation. The experiments were carried out to verify the FEA, and acceptable results can be achieved. Originality/value: This paper proposed a novel IPMSM with the double-layer permanent magnets, which is designed and checked by the multi-physics fields, and the high efficiency in all operational regions can be achieved for this machine.